PHOSPHORUS: FROM THE NUTRIENT TO POLLUTANT! - Klein, Claudia; Agne, Sandra Aparecida Antonini (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706430 Phosphorus is an essential element for plants and animals. The nutrient is widely used incultivation areas, but when applied to the soil in high quantities have pollution potential especiallyin surface waters, but Brazilian law does not recognize with polluter. When contaminant causeeutrophication of waters and fish kills. Phosphorus is difficult to recover, but control measures asconservation practices, sizing and use of fertilizer plants extractors (pasture) can be used. Theobjective of the review was to present the basic aspects of the dynamics of phosphorus in the soil,and use as nutrient pollution potential.